2020
DOI: 10.20546/ijcmas.2020.902.156
|View full text |Cite
|
Sign up to set email alerts
|

Partial Purification and Characterization of Proteases from the Visceral Waste of Indian Major Carp, Labeo rohita (Hamilton, 1822)

Abstract: Acidic and alkaline proteases from visceral waste of Labeo rohita (Hamilton, 1822) were isolated, partially purified by ammonium sulphate precipitation followed by dialysis, their kinetics and characteristics studied. The purification fold increased from 1.24 to 2.49 and 1.19 to 1.55 in acidic and alkaline protease respectively along the purification steps. The molecular weight was found in the range of 15-35 kDa and 25-63 kDa respectively in acidic and alkaline proteases. The pH and temperature optima for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Previamente, se ha reportado que los extractos con actividad pepsina de los peces de agua dulce sábalo (Prochilodus lineatus), surubí (Pesudoplatistoma sp. ), pez disco (Symphysodon aequifasciata), carpa india mayor (Labeo rohita) exhibieron actividades 43,4; 205; 0,64 y 2,9 U mg -1 frente al sustrato hemoglobina ácida (Acevedo Gomez et al 2018:2019b, Chong et al 2002, Mohanty et al 2020). En este trabajo, los resultados obtenidos para el EP de pacú evidenciaron un valor intermedio entre los informados por la literatura.…”
Section: Resultados Y Discusiónunclassified
See 1 more Smart Citation
“…Previamente, se ha reportado que los extractos con actividad pepsina de los peces de agua dulce sábalo (Prochilodus lineatus), surubí (Pesudoplatistoma sp. ), pez disco (Symphysodon aequifasciata), carpa india mayor (Labeo rohita) exhibieron actividades 43,4; 205; 0,64 y 2,9 U mg -1 frente al sustrato hemoglobina ácida (Acevedo Gomez et al 2018:2019b, Chong et al 2002, Mohanty et al 2020). En este trabajo, los resultados obtenidos para el EP de pacú evidenciaron un valor intermedio entre los informados por la literatura.…”
Section: Resultados Y Discusiónunclassified
“…El rango de pHs con actividad enzimática del EP de pacú (pHs 1,0 a 3,5) resultó similar a lo reportado para los extractos de surubí, lenguado y jaurel amarillo (Candiotto et Silva et al 2022b). La determinación del pH óptimo de una enzima es esencial ya que constituye un indicador para su potencial aplicación en diferentes procesos (Mohanty et al 2020). Estos resultados indican que tanto el EP, como las pepsinas de pacú, podrían ser utilizadas para la hidrólisis de proteínas alimentarias.…”
Section: Resultados Y Discusiónunclassified
“…The result suggested that the endogenous proteinase enzymes in beardless barb muscle were able to hydrolyse its muscle proteins at high salt concentration but to a lesser than that with the absence of salt. The relative enzyme activity from visceral waste of Labeo rohita showed a decrease of more than 50% for both acidic and alkaline proteases at NaCl concentration of 0.5% (Mohanty et al ., 2020). Vannabun et al .…”
Section: Resultsmentioning
confidence: 99%
“…Contents available at Journals Home Page: www.ijzi.net Prachumratana, 2008), catalyses the hydrolysis of long-chain triacylglycerols to form glycerol and fatty acids. Microbial lipases are one of the most essential extracellular enzymes that have drawn the interest of scientists for years due to their broad biotechnological applications (Mohanty et al, 2020). Microbial enzymes have achieved worldwide recognition for their widespread use in diverse sectors of industry.…”
Section: International Journal Of Zoological Investigations Issn: 245...mentioning
confidence: 99%